Analysis of Subsidized Fertilizer Distribution (Case Study on Rice Farmers in Kendari City) - Batoa, Hartina; Rosmawaty, Rosmawaty; Mardin, Mardin; Jayadisastra, Yoenita; Lasinta, Megafirmawanti; Harnas, Sitti (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2021)
This study aims to determine the effectiveness of fertilizer delivered to farmers in Baruga Village, Kendari City, with a subsidy. To evaluate the point, the five principles (5T) are used: the appropriate place, the appropriate type, the appropriate quantity, the appropriate time, and the reasonable price. Information was gathered from 24 farmers who received government-subsidized fertilizer through a questionnaire. The sample size is determined by simple random sampling, 10% of the number of farmers receiving subsidized fertilizer, or 240 farms. The percentage of correct responses for each of the five principles was calculated to examine the data. In Kelurahan Baru, Kendari City, the effectiveness of subsidized fertilizer delivery was judged to be 67.50 percent. Baruga was chosen as the research site because it received the most subsidized fertilizers at the district/city level in Southeast Sulawesi.